Mobile Hawkers in Cities: A local wisdom and its impact on urban planning sustainability - Erma Fitria Rini; Rufia Andisetyana Putri; Murtanti Jani Rahayu; Lintang Suminar (Local Wisdom : Jurnal Ilmiah Kajian Kearifan Lokal, 2024)
Mobile hawkers play an important role in providing accessible products, particularly to the urban community. For years, traditional on-demand vegetable hawkers have been benefiting from local wisdom. The presence of mobile hawkers who come to costumers has the potential to reduce community movements by shortening the distance that customer must travel to shop. By reducing the length travelled in daily shopping, it is possible to reduce the usage of motorized vehicles, which has a further impact on urban sustainability. The purpose of this research is to compare the environmental impact of community activities with and without mobile hawkers on daily shopping activities. In this research, the Wilcoxon test was employed to determine whether there is a mean difference between two paired samples. The results reveal that mobile hawkers can help reduce the carbon footprint of community daily shopping mobility.